Analysis of physiological, biochemical mechanism, and pigment related genes in leaf and petal coloration of Paeonia qiui - Shanrong Dong; Shuiyan Yu; Zihan Yang; Yingan Niu; Xinyue Liu; Chenxi Wei; Jianrang Luo (Ornamental Plant Research)
In addition to flower color, the red new leaves of tree peonies in spring are also ornamental, with the leaf color of Paeonia qiui being the most typical. This study aimed to explore the formation mechanism of P. qiui leaf and flower color by quantitative evaluation and correlating the factors affecting the coloration of leaves and petals. Leaves from eight developmental stages, and petals from five developmental stages of P. qiui were collected for determination of color parameter, cellular pH, anthocyanin, anthoxanthin, chlorophyll, and carotenoid contents, and it was found that anthocyanins and chlorophylls were closely related to leaf coloration, with anthocyanins being the determinant of leaf red color, while anthocyanidins and anthoxanthins affect the petal coloration, with anthocyanins being more influential. High-performance liquid chromatography (HPLC) analysis showed that leaves contain peonidin-3,5-di-O-glucoside (Pn3G5G), peonidin-3-O-glucoside (Pn3G), and cyanidin-3,5-di-O-glucoside (Cy3G5G), and petals contain Pn3G5G, Pn3G, Cy3G5G, and pelargonidin-3,5-di-O-glucoside (Pg3G5G), with Pn3G5G being the most abundant in both leaves and petals. qRT-PCR analysis revealed that PqDFR, PqANS, and PqMYB113 significantly and positively correlated with anthocyanin accumulation in leaves, and PqF3H promoted anthocyanin accumulation to a greater extent in petals. The findings of this study can provide a theoretical reference for the cultivation of new tree peony varieties and germplasm innovation.